Apichatpong Weerasethakul Sourcebook the serenity of madness - Apichatpong Weerasethakul 1970- (Independent Curators International, 2016)
Offering a fresh perspective on the work of internationally acclaimed filmmaker Apichatpong Weerasethakul (born 1970), the Apitchapong Weerasethakul Sourcebook moves between scientific documents and personal documentary, interviews and epistolary dialogue, the cinematic and the poetic. In its multimodal approach the Sourcebook reflects Weerasethakul's artistic practice in which he portrays the everyday alongside supernatural elements while suggesting a distortion between fact and folklore, history and storytelling. Weerasethakul's personal writings and interviews, much of which is translated here for the first time, draw out his deep commitment to stories often excluded in history in and out of Thailand: voices of the poor and the ill, marginalized beings and those silenced and censored for personal and political reasons. The Sourcebook includes materials on such topics as implanted memories in mice, caves in Laos left over from the Indochina wars, new methods for listening underwater and meditations on light and darkness, plus interviews between Weerasethakul and leading art historians as well as texts drawn from his personal library. The Sourcebook invites readers into Weerasethakul's intimate exploration of his influences--in his words, "like [a] stream of consciousness, suffocated by the data."
Published in conjunction with a touring exhibition
Keywords: Apichatpong Weerasethakul -- 1970-; Apichatpong Weerasethakul / 1970-; Ausstellungskatalog